A high-density relativistic reflection origin for the soft and hard X-ray excess emission from Mrk 1044. Issue 1 (6th June 2018) - Mallick, L; Alston, W N; Parker, M L; Fabian, A C; Pinto, C; Dewangan, G C; Markowitz, A; Gandhi, P; Kembhavi, A K; Misra, R
ABSTRACT: We present the first results from a detailed spectral-timing analysis of a long (∼130 ks) XMM–Newton observation and quasi-simultaneous NuSTAR and Swift observations of the highly accreting narrow-line Seyfert 1 galaxy Mrk 1044. The broad-band (0.3 – 50 keV) spectrum reveals the presence of a strong soft X-ray excess emission below ∼1.5 keV, iron Kα emission complex at ∼6–7 keV and a 'Compton hump' at ∼15–30 keV. We find that the relativistic reflection from a high-density accretion disc with a broken power-law emissivity profile can simultaneously explain the soft X-ray excess, highly ionized broad iron line and the Compton hump. At low frequencies ([2 − 6] × 10 −5 Hz), the power-law continuum-dominated 1.5–5 keV band lags behind the reflection-dominated 0.3–1 keV band, which is explained with a combination of propagation fluctuation and Comptonization processes, while at higher frequencies ([1 − 2] × 10 −4 Hz), we detect a soft lag which is interpreted as a signature of X-ray reverberation from the accretion disc. The fractional root-mean-squared variability of the source decreases with energy and is well described by two variable components: a less variable relativistic disc reflection and a more variable direct coronal emission. Our combined spectral-timing analyses suggest that the observed broad-band X-ray variability of Mrk 1044 is mainly driven by variations in the location or geometry of the optically thin, hot corona.